EMMANUEL DE MARTONNE ET LA NAISSANCE DE LA GRANDE ROUMANIE - GAVIN BOWD (Revue Roumaine de Géographie)
The research of Emmanuel de Martonne (1873–1955) in the field of physical goegraphy, in its many forms, made him the leading geographer, not only in France, but on an international level. His immense body of work also covers human geography : La Valachie, a doctoral thesis published in 1902, remains a model of the Vidalian regional monograph. But it must be pointed out that de Martonne’s work is not limited to a strictly scientific and disinterested domain. By its very nature, his geographical work is bound up with history, and therefore political circumstances, something whichis clearly displayed in his long and passionate relationship with Romania. It is before the Great War, on the frontier between Hungary and Romania, that Emmanuel de Martonne begins his work as a geographer. Enamoured of a landscape and a people, this eminent scholar will serve the cause of ‘Greater Romania’ : firstly as a supporter of Romanian intervention in the European conflict, then as a ‘drawer of frontiers’ at the Versailles Peace Conference. Here we see how geography can be used in political projects, rivalries over territories and debates on identity.